Makna Kasih Persaudaraan Kristiani: Refleksi Teologis - Spiritual - Praktis - Angelo Luciani Moa Dosi Woda (Pusat Riset dan Inovasi Nasional, 2024)
In the midst of fast-paced times and the spread of various views, it feels like people are starting to forget the meaning of Christian brotherhood. It is as if the spirit of loving our fellow brothers and sisters like the Lord Jesus loved us is fading away. Now, modern humans are more likely to be